ULTRA-LOW INTENSITY PROTON BEAMS FOR RADIATION RESPONSE RELATED EXPERIMENTS AT THE U-120M CYCLOTRON - Tomas Matlocha; Filip Krizek (Acta Polytechnica CTU Proceedings)
The U-120M cyclotron at the Nuclear Physics Institute (NPI) of the Czech Academy of Sciences in Rez is used for radiation hardness tests of electronics for high-energy physics experiments. These tests are usually carried out with proton fluxes of the order of 105–109 proton·cm−2·s−1. Some tests done for the upgrade of the Inner Tracking System of the ALICE experiment at CERN, however, required proton beam intensities several orders of magnitude lower. This paper presents a method which has been developed to achieve the proton beam flux of the order of 1 proton · cm−2·s−1. The method is mainly based on reduction of the discharge current in the cyclotron internal Penning type ion source. Influence of this new operation mode on the lifetime of ion source cathodes is discussed.